ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA PADA MATERI SEGIEMPAT DITINJAU DARI SELF-REGULATED LEARNING - Riri Ropidatul Fadilah; Nuranita Adiastuty; Sumarni Sumarni (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2021)
This study aims to describe students' self-regulated learning level and students' mathematical connection ability for each self-regulated learning level. The topic used is quadrilateral. This is qualitative research with descriptive method. Study took place at Desa Ancaran Kec./ Kab. Kuningan, West Java, with subjects consisting of six seventh grade SMP/MTs students. Data is collected using questionnaires, tests, interviews, and documentation. Questionnaire and mathematical connection ability tests were given to all six subjects. After collecting data, analysis is performed with steps: data reduction, data presentation, and drawing conclusions. Result shows that out of six subjects, 1 student is classified high in self-regulated learning category and 5 other students are classified average in self-regulated learning category. Out of three selected subjects, 1 student with high level of self-regulated learning has connection ability in good category, while 2 students with average level of self-regulated learning have mathematical connections in sufficient category. Student with high level of self-regulated learning can fulfill three of the five indicators of mathematical connection ability, 1 student with average self-regulated learning can fulfill two indicators, and 1 student with other self-regulated learning can fulfill one indicator of mathematical connection.Keywords: Mathematical Connection Ability, Self-Regulated Learning, Quadrilateral